Penguasaan Konsep Fisika Peserta Didik melalui Pembelajaran Inkuiri Terbimbing Terintegrasi Peer Instruction dan Modul Digital - Lamia Ulfa; I Wayan Gunada; Hikmawati (Mataram University, 2026)
This study aimed to determine the effect of guided inquiry learning integrated with peer instruction assisted by digital modules on students’ mastery of physics concepts in the topic of sound waves. The research employed a quasi-experimental method using a nonequivalent control group design. The population of the study consisted of all eleventh-grade students at SMAN 1 Kuripan. The sample was selected using purposive sampling, resulting in class XI-2 as the experimental class and class XI-1 as the control class. The experimental class received guided inquiry learning integrated with peer instruction assisted by digital modules, while the control class was taught using conventional learning methods. Data collection was conducted using essay tests to measure students’ concept mastery through pretests and posttests. The data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain analysis. The average pretest scores of concept mastery in the experimental and control classes were 27.33 and 28.33, respectively, while the posttest scores were 74.27 and 63.10. The results of the normality and homogeneity tests indicated that the data were normally distributed and homogeneous. Furthermore, hypothesis testing using the t-test showed that the calculated t-value was higher than the table t-value, where t_calculated = 2.49 and t_table = 2.00. Therefore, H₀ was rejected and Hₐ was accepted. In addition, the N-Gain analysis showed that the improvement in concept mastery in the experimental class was higher than that in the control class. Thus, guided inquiry learning integrated with peer instruction assisted by digital modules can be used as an innovative learning alternative to improve students’ mastery of physics concepts.